Managerial ability and firm performance: Evidence from an emerging market - Aamir Inam Bhutta; Muhammad Fayyaz Sheikh; Aroosa Munir; Arooj Naz; Iqra Saif (Cogent Business & Management, 2021)
This study empirically examines the impact of managerial ability on firm performance. Using the sample of 246 firms listed at Pakistan Stock Exchange during 2009 to 2017, this study finds that more able managers significantly increase the firm performance while less able managers significantly reduce the firm performance. These findings hold for both accounting and market measures of firm performance as well as alternative measures of managerial ability. Further, we control for endogeneity and cross-sectional variation issues using 2SLS and Fama-MacBeth methods, respectively. Overall, we conclude that able managers enhance the firm value, and the effects are stronger in financially constrained firms. This study provides fresh evidence that able managers bring intangible resources in the firms, which positively contribute to the firm performance even in the challenging environment and the weak legal systems.
Keywords: 650; Firm performance; managerial ability; fixed effects; 2SLS Pakistan